Poverty and Worklessness in Britain. - Nickell, S (Centre for Economic Performance, LSE, 2003)
Relative poverty in the UK has risen massively since 1979 mainly because of increasing worklessness, rising earnings dispersion and benefits indexed to prices, not wages. So poverty is now at a very high level. The economic forces underlying this are the significant shift in demand against the unskilled which has outpaced the shift in relative supply in the same direction. This has substantially weakened the low-skill labour market which has increased both pay dispersion and worklessness, particularly among low-skilled men. The whole situation has been exacerbated by the very long tail in the skill distribution, so that over 20 per cent of the working age population have very low skills indeed (close to illiterate). Practical policies discussed include improving education and overall well-being for children in the lower part of the ability range, raising wage floors, New Deal policies, tax credits and benefits for the workless. Overall, I would argue that without reducing the long tail in the skill distribution, there is no practical possibility of policy reducing relative poverty to 1979 levels.